Extended Rayleigh Damping Model - Nakamura, Naohiro (Frontiers in Built Environment, 2016)
In dynamic analysis, frequency domain analysis can be used if the entire structure is linear. However, time history analysis is generally used if nonlinear elements are present. Rayleigh damping has been widely used in time history response analysis. Many articles have reported the problems associated with this damping and suggested remedies. A basic problem is that the frequency area across which the damping ratio is almost constant is too narrow. If the area could be expanded while incurring only a small increase in computational cost, this would provide an appropriate remedy for this problem. In this study, a novel damping model capable of expanding the constant frequency area by more than five times was proposed based on the study of a causal damping model. This model was constructed by adding two terms to the Rayleigh damping model and can be applied to the linear elements in the time history analysis of a nonlinear structure. The accuracy and efficiency of the model were confirmed using example analyses.